Using scenario planning as a methodology for analysis in three sectors of the interactive digital media marketplace - Yang, Yi (2011)
In this thesis, a scenario planning approach, which is a synthesis of the three main schools of thought in the area, is used as a methodology for analysis. The approach aims to study the future of Interactive Digital Media (IDM) applications such as online music, on- demand television and massively multi-player online role-playing games (MMORPG). More specifically, the research addresses the question of what constitutes a win-win scenario for players in the IDM market. Following this, what are the policy implications for such a scenario and its alternatives? The synthesized approach, while essentially qualitative in nature, nevertheless draws from the rigors of the quantitative school in identifying and then tracking the significant dimensions of analysis that connect over time into strands of events leading to plausible scenarios. The tracking tool used to log event triggers is a customization or configuration of an off-the- shelf web crawler with analytic functions. The tool supports morphological analysis by mapping strands to themes such as content ownership, technical platform, distribution channel, product/service innovation, and consumer behavior. Results of a six-month empirical tracking of developments in three IDM sectors are analyzed using a variation of Multi-Dimensional Scaling (MDS). It is demonstrated that this synthesized scenario planning methodology is useful and practical for monitoring the rapidly growing interactive digital media market-space. Further insights and policy implications, which are obtained from empirical research that address win-win and other less desirable scenarios in the IDM marketplace, are formulated from the results.